Treatment of Chitosan Modified-composite Polyamide Membranes by Sodium Hypochlorite for Enhancing Antifouling Property - Quan, Duong Xuan; Dung, Tran Thi; Thu, Ngo Hong Anh (VNU Journal of Science: Natural Sciences and Technology; Vol 40 No 1, 2023)
To enhance the antifouling resistance, this study modified commercial thin-film composite polyamide membranes with chitosan by redox-initiated graft polymerization process before treating the modified membrane’s surface using sodium hypochlorite. The surfaces of the modified membranes were characterized using field emission scanning electron microscopy, and attenuated total reflection - Fourier transform infrared spectroscopy. The membranes’ performance and fouling resistance were shown through flux, retention, and maintained flux ratios during the filtration of calcium chloride solution. In addition, the antibacterial ability of membranes was evaluated through the growth of bacteria on their surface, and the anti-biofouling resistance of these membranes was evaluated through the maintained flux ratios, irreversible antifouling factor, and flux after 90-minute filtration of actual river water. The results showed that the modified membrane had superior antibacterial ability compared to the original membrane. Additionally, although the flux was reduced slightly, the modified membrane treated with NaClO exhibited a remarkable improvement in the maintained flux ratios (up to 99%) and the irreversible antifouling factor (~ 100%). This is similar to the filtration of actual river water, the chitosan-grafted polyamide membrane after NaClO treatment was shown to be more effective than the unmodified membrane in reducing the fouling phenomenon.